Learning Planning Cooperative Based on Emotional Approach - Muharam, Suhari; Sobri, Ahmad Yusuf (Proceedings Series of Educational Studies, 2024)
Learning planning is a crucial component in achieving educational goals, especially in the context of cooperative learning at various levels of education. This study aims to explore cooperative learning planning based on teachers' emotional approach in SMKN 14 Jakarta. The researcher used a qualitative approach with a case study research design. This case study research is conducted in-depth on the emotional approach of teachers in the classroom with the aim of obtaining a complete and in-depth picture of an entity through the data collected. The results of this study show several findings carried out by teachers in designing emotional approach-based cooperative learning, namely: (1) determining the material to be discussed through discussion, (2) making class agreements together, (3) ensuring each group is actively involved in doing the task, (4) making sure to look for additional references as needed, (5) studying and listening to friends' presentations. The findings show that teachers have created an inclusive learning environment that is responsive to learners' needs and emotional conditions.